2015
DOI: 10.3389/fpsyg.2015.00042
|View full text |Cite
|
Sign up to set email alerts
|

Using eye tracking to test for individual differences in attention to attractive faces

Abstract: We assessed individual differences in visual attention toward faces in relation to their attractiveness via saccadic reaction times. Motivated by the aim to understand individual differences in attention to faces, we tested three hypotheses: (a) Attractive faces hold or capture attention more effectively than less attractive faces; (b) men show a stronger bias toward attractive opposite-sex faces than women; and (c) blue-eyed men show a stronger bias toward blue-eyed than brown-eyed feminine faces. The latter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 63 publications
4
49
0
Order By: Relevance
“…Relatively, facial attractiveness in male faces is not as important for women as is facial attractiveness in female faces for men. Although women showed attention bias toward HA male faces compared with LA male faces (Silva et al, 2016), the attentional bias toward HA oppositesex faces was significantly stronger for men than that for women (Kleck and Rubenstein, 1975;Fugita et al, 1977;van Straaten et al, 2010;Valuch et al, 2015;Mitrovic et al, 2018). Nevertheless, we should notice that the attractiveness in male faces may be different for women in different situations (e.g., in the ovulatory phase or not).…”
Section: Comparison Of the Cognitive Processing Of Facial Attractivenmentioning
confidence: 76%
See 3 more Smart Citations
“…Relatively, facial attractiveness in male faces is not as important for women as is facial attractiveness in female faces for men. Although women showed attention bias toward HA male faces compared with LA male faces (Silva et al, 2016), the attentional bias toward HA oppositesex faces was significantly stronger for men than that for women (Kleck and Rubenstein, 1975;Fugita et al, 1977;van Straaten et al, 2010;Valuch et al, 2015;Mitrovic et al, 2018). Nevertheless, we should notice that the attractiveness in male faces may be different for women in different situations (e.g., in the ovulatory phase or not).…”
Section: Comparison Of the Cognitive Processing Of Facial Attractivenmentioning
confidence: 76%
“…Neurophysiological also revealed that HA opposite-sex faces induced a larger LPP than did LA faces among heterosexual individuals (van Hooff et al, 2011). Nevertheless, although some researchers have found attentional bias toward HA male faces among female observers, they also indicate that such an effect is much weaker than the attentional bias toward HA female faces among male observers (van Straaten et al, 2010;Valuch et al, 2015). The difference between the hypotheses of "female beauty captures attention" and "opposite-sex beauty captures attention" requires further investigation.…”
Section: Comparison Of the Cognitive Processing Of Facial Attractivenmentioning
confidence: 91%
See 2 more Smart Citations
“…Separate LME models were built for dependent variables of perceived (a) politeness, (b) appropriateness, and (c) usage. In all cases, we first defined a base model, which included only one random effect (Subject); refined models were then identified by performing comparisons using the ANOVA function in R, and systematically comparing the full model with the model reduced by random and fixed effects in turn (see similar approach in Valuch et al, 2015). Our fixed effects included Intention (LIE, BLUNT) and Cultural Group (Canadian, Chinese, German), Age, Cloze, Education, Self-Rating Language Scores, and Duration in Canada.…”
Section: Discussionmentioning
confidence: 99%